A dynamic network analysis of emergent grammar. Issue 6 (December 2019) - Ibbotson, Paul; Salnikov, Vsevolod; Walker, Richard
For languages to survive as complex cultural systems, they need to be learnable. According to traditional approaches, learning is made possible by constraining the degrees of freedom in advance of experience and by the construction of complex structure during development. This article explores a third contributor to complexity: namely, the extent to which syntactic structure can be an emergent property of how simpler entities – words – interact with one another. The authors found that when naturalistic child directed speech was instantiated in a dynamic network, communities formed around words that were more densely connected with other words than they were with the rest of the network. This process is designed to mirror what we know about distributional patterns in natural language: namely, the network communities represented the syntactic hubs of semi-formulaic slot-and-frame patterns, characteristic of early speech. The network itself was blind to grammatical information and its organization reflected (a) the frequency of using a word and (b) the probabilities of transitioning from one word to another. The authors show that grammatical patterns in the input disassociate by community structure in the emergent network. These communities provide coherent hubs which could be a reliable source of syntactic information for the learner. These initial findings are presented here as proof-of-concept in the hope that other researchers will explore the possibilities and limitations of this approach on a larger scale and with more languages. The implications of a dynamic network approach are discussed for the learnability burden and the development of an adult-like grammar.